The collapse behaviour of tapered steel beams - Mandal, Satya Narayan (1978)
In this thesis, the collapse mode of failure of tapered steel beams is examined for three different loading cases. Firstly, for the case when the beam is loaded inside the tip; secondly, when the beam is loaded outside the tip, and thirdly, when the beam is loaded at the tip. The theoretical collapse mode of failure presented here provides an identical collapse load whether obtained from lower or upper bound solutions. Fourteen tests on tapered steel beam specimen were carried out to examine the collapse modes of failure and their ultimate strengths for steel tapered beams loaded inside, outside and at the tip. The experimental collapse loads and their collapse modes of failure are compared with theoretically predicted collapse loads and the proposed collapse mechanisms respectively.